2017
DOI: 10.1021/jacs.6b09681
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Tunable Metal-Mediated Hydrolysis of Amyloid-β Peptides

Abstract: An amyloidogenic peptide, amyloid-β (Aβ), has been implicated as a contributor to the neurotoxicity of Alzheimer's disease (AD) that continues to present a major socioeconomic burden for our society. Recently, the use of metal complexes capable of cleaving peptides has arisen as an efficient tactic for amyloid management; unfortunately, little has been reported to pursue this strategy. Herein, we report a novel approach to validate the hydrolytic cleavage of divalent metal complexes toward two major isoforms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 60 publications
1
68
0
Order By: Relevance
“…Therefore, inhibition of Aβ aggregation has been considered a promising approach to relieve the symptoms of AD . Most of the existing inhibitors mainly focus on a simple way to suppress Aβ aggregation, such as monomer binding, oxidizing, hydrolyzing, thermal depolymerizing, etc. Photooxygenation of Aβ has emerged as an effective way to inhibit Aβ aggregation due to the spatiotemporal controllability of light and the ability to prevent Aβ reassembly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inhibition of Aβ aggregation has been considered a promising approach to relieve the symptoms of AD . Most of the existing inhibitors mainly focus on a simple way to suppress Aβ aggregation, such as monomer binding, oxidizing, hydrolyzing, thermal depolymerizing, etc. Photooxygenation of Aβ has emerged as an effective way to inhibit Aβ aggregation due to the spatiotemporal controllability of light and the ability to prevent Aβ reassembly.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Amyloid b (Ab)a ggregation has been regarded as the pathological hallmarko fA D, and metal ions, such as Cu, Zn, Fe, can accelerate Ab aggregation and result in neurotoxicity. [2] Therefore, inhibition of Ab aggregation has been considered a promising approach to relieve the symptomso fA D. [3] Most of the existing inhibitors mainly focuso nas imple way to suppress Ab aggregation, [4][5][6][7][8][9] such as monomer binding, oxidizing, [4] hydrolyzing, [5] thermald epolymerizing, [6] etc. Photooxygenationo fA b has emerged as an effective way to inhibitA b aggregation due to the spatiotemporal controllability of light and the ability to prevent Ab reassembly.C urrently,A b photooxidantsc an be divided into two categories:s mallm olecules [4, 10] and nanoparticles.…”
mentioning
confidence: 99%
“…First of all, the hydrolytic ability of MoS 2 –Co towards Aβ 40 monomers was determined by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) assay . Human insulin was utilized as an internal standard to acquire quantitative information from MALDI‐TOF MS .…”
Section: Methodsmentioning
confidence: 99%
“…Cyclen is a metal chelator and has potential to disaggregate the metal-induced Ab aggregates as previously reported. 25,26,31 The chelating ability of SiO 2 -cyclen nanochelator was determined by ICP-MS aer incubation with Cu 2+ and Zn 2+ . The Cu and Zn amounts aer reacting with SiO 2 -cyclen were 22.18 AE 0.33 and 22.48 AE 0.29 mg mg À1 in terms of SiO 2 -cyclen weight, respectively.…”
Section: Chelation With Cu 2+ or Zn 2+mentioning
confidence: 99%
“…24 We and other researchers ever reported that macrocyclic chelator 1,4,7,10-tetraazacyclododecane (cyclen) could reduce the metal-induced Ab aggregation and neurotoxicity. 25,26 However, the hydrophilic cyclen (water solubility: 999 g L À1 ) may be hard to cross the BBB.…”
Section: Introductionmentioning
confidence: 99%